Juridical Review of Net Revenue Sharing and Profit Sharing Implementation In Islamic Bank - Hermansyah; Febriadi, Sandy Rizki (UPT Publikasi Ilmiah UNISBA, 2024)
Islamic economic and financial systems are based on the achievement of justice and equitable distribution of economic welfare as well as universal ethical values that can be accepted by various parties. This study aims to determine the legal basis for the application of net revenue sharing and profit sharing methods in Islamic banks. The method used is normative juridical approach, data collection techniques using literature study and field study, data analysis using qualitative normative analysis. The results mentioned that the regulation of net revenue sharing and profit sharing of Islamic banks in Indonesia is contained in Article 26 of Law Number 21 of 2008 concerning Islamic Banking on the operational principles of Islamic banks, DSN MUI fatwa Number 15/DSN-MUI/IX/2000 on the principle of distribution of business results in Islamic financial institutions and PBI Number 7/46/PBI/2005 concerning the collection of funds and distribution of funds for parties carrying out business activities based on sharia principles.